Optimisation of a whole blood flow cytometry assay to aid in the diagnosis of tuberculosis by detecting intracellular cytokines released by CD4+ T-cells - Snyders, Candice Irene (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017